LONG-LIVED BONE MARROW PLASMA CELLS DURING IMMUNE RESPONSE TO ALPHA (1→3) DEXTRAN - I. N. Chernyshova (SPb RAACI, 2015)
Production kinetics and some functional properties of long-lived marrow plasma cells were studied in mice immunized with T-independent type 2 antigens. Alpha (1→3) dextran was used as an antigen for immunization. The mice were immunized by dextran, and the numbers of IgM antibody producing cells were determined by ELISPOT method. The cell phenotype was determined by cytofluorimetric technique. In the area of normal bone marrow lymphocytes ~4% of T and ~85% of B cells were detected. About 35% of the cells expressed a plasmocyte marker (CD138); 3% were CD138+IgM+, and about 6% of the lymphocytes were double-positive for CD138+IgA+. Among spleen lymphocytes, 50% of T and 47% of B cells were detected. About 1.5% lymphocytes were CD138+, and 0.5% were positive for CD138 and IgM. Time kinetics of antibody-producing cells in bone marrow and spleen was different. In spleen populations, the peak amounts of antibody-secreting cells have been shown on the day 4; the process abated by the day 28. Vice versa, the numbers of the antibody-producing cells in bone marrow started to increase on the day 4. The process reached its maximum on day 14, and after 28th day became stationary. The in vitro experiments have shown that supplementation of bone marrow cells from immune mice with dextran did not influence their functional activity. It was previously shown for cells responding to T-dependent antigens only. A specific marker for the long-lived plasma cells is still unknown. However, these cells possess a common CD138 marker specific for all plasma cells. A method for isolation of bone marrow CD138+ cells was developed. The CD138+ cells were of 87-97% purity, being enriched in long-lived bone marrow cells, and produced monospecific antibodies.